EWSR1-PATZ1 fusion renal cell carcinoma: a recurrent gene fusion characterizing thyroid-like follicular renal cell carcinoma - Al-Obaidy, Khaleel I; Bridge, Julia A; Cheng, Liang; Sumegi, Janos; Reuter, Victor E; Benayed, Ryma; Hameed, Meera; Williamson, Sean R; Hes, Ondrej; Alruwaii, Fatimah I; Segal, Jeremy P; Wanjari, Pankhuri; et al. (Modern pathology, 2021)
Thyroid-like follicular renal cell carcinoma is an uncommon kidney tumor with no distinct molecular alteration described to date. This cohort of eight women with mean and median ages of 45 and 46 years, respectively (range 19-65 years), had unencapsulated, well-circumscribed tumors composed of tightly packed anastomosing follicle-like cysts filled with eosinophilic colloid-like material and lined by cuboidal cells with high nuclear to cytoplasmic ratios, oval to elongated nuclei with perpendicular arrangement toward the lumens, and prominent nuclear overlapping. The stroma between these was minimal with the exception of two tumors. Calcifications and necrosis were absent. Immunohistochemically, the tumors were positive for KRT19 (7/7), PAX8 (5/5), cyclin D1 (6/6), KRT7 (5/7), and AMACR (1/5; focal, weak), and were negative for WT1, TTF1 (transcription termination factor-1), and thyroglobulin. In three of three tumors tested molecularly, EWSR1-PATZ1 fusion was identified by RNA sequencing and confirmed by RT-PCR and Sanger sequencing. Over a follow-up period of 1-7 years, no evidence of recurrence or metastasis has been detected. The EWSR1-PATZ1 fusion has been recognized as a recurrent alteration in a subset of round to spindle cell sarcomas with EWSR1-non-ETS fusions (EWSR1-PATZ1 sarcoma) and in several central nervous system tumors. The finding of an EWSR1-PATZ1 fusion in all three of the thyroid-like follicular renal cell carcinomas for which sufficient tissue was available for genomic profiling provides the first distinct molecular abnormality in thyroid-like follicular renal cell carcinomas, supporting its designation as a distinct diagnostic entity.
Keywords: onkogenní fúze; Carcinoma, Renal Cell; Repressor Proteins; lidé; Middle Aged; Adult; transkripční faktory Krüppel-like; Kidney Neoplasms; karcinom z renálních buněk; represorové proteiny; Female; protein EWS vázající RNA; Humans; Oncogene Fusion; nádory ledvin; lidé středního věku; mužské pohlaví; mladý dospělý; Kruppel-Like Transcription Factors; ženské pohlaví; Young Adult; RNA-Binding Protein EWS; Male; Aged; dospělí; senioři